A study of anatomical variants of the facial artery and their use in facial flap surgery - Rossell Perry, Percy (2009)
Introduction: Several reports about facial artery anatomy have been published in the literature, however none of such studies has ever been performed in our country. Flaps based on the facial artery, like those described by Pribaz in 1992, are a good alternative for the management of severe palatal fistula management. On the other hand, the reconstruction of facial wounds after skin cancer resection is commonly needed, and it requires selected surgical techniques in order to improve facial cosmetics and functioning in our patients. In this paper we describe our experience using these flaps and we propose a modification for the technique. Objetives: show the anatomical variants in facial artery anatomy in Peruvian cadavers and their application in facial flap surgery based on this artery. Material and method: This is an analytic and descriptive study. 24 half-faces from 12 Peruvian cadavers (10 men and two women) were manually dissected, and thy were macroscopically and microscopically observed by the author. The facial artery was dissected from its origin in the face, at the lower border of the mandible, up to its terminal branches. We describe the anatomical variants about the facial artery localization and its perforating cutaneous branches. Also, we include in this report a retrospective study performed in 23 patients who underwent reconstructive surgery for many different reasons using flaps based on the facial artery. Results: The study in cadavers showed the predominance of a nasal pattern in the way of the facial artery in Peruvian cadavers (70.8 %). Also, the cadaver dissection showed a variable number of skin perforating branches distributed along the way of the facial artery in all cases. Flaps techniques used for facial wound repair and palatal fistulae had good outcomes in most of the cases.   Conclusions: A nasal pattern for the way of the facial artery is the most commonly observed in our study performed in Peruvian cadavers. Skin perforating branches of the facial artery are constantly present along the way of the facial artery, which guarantees the design of the surgical flap. Most operations performed using flaps based on the facial artery were successful, with a low percentage of complications.